Analisis Faktor yang Mempengaruhi Kinerja Keuangan PT Gudang Garam Tbk Tahun 2019-2022 - Intan Pandini; Hwihanus Hwihanus (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to analyze the financial performance of PT Gudang Garam Tbk during the period from 2019 to 2022, with a focus on the company's financial statements. The evaluation is conducted by understanding the assets and liabilities of the company, especially current assets, non-current assets, and net exposure. The significant increase in cash and cash equivalents reflects efficient liquidity management, while fluctuations in trade receivables and inventory highlight operational challenges. Sustained investments in fixed assets signify a commitment to long-term growth, although fluctuations in trade payables and short-term liabilities demand caution. The consistently positive net exposure provides insight into potential growth and financial stability. However, the decrease in net exposure in 2021 indicates the impact of changing dynamics in the cigarette industry. In conclusion, a comprehensive understanding of financial statements is crucial for identifying opportunities and risks, providing a foundation for informed strategic decision-making. Additionally, this research emphasizes the importance of a deep understanding of factors influencing financial performance. Focus on liquidity, fixed asset investment, and net exposure management provides a complete picture of the company's dynamics. In facing the changing dynamics of the cigarette industry, the company needs to maintain a balance between long-term growth and financial risk management. The results of this research can serve as a valuable guide for the company's strategic decision-making in the future.